BRAF V600E potentially determines "Oncological Resectability" for "Technically Resectable" colorectal liver metastases. (18th September 2021) - Kobayashi, Shin; Takahashi, Shinichiro; Nomura, Shogo; Kojima, Motohiro; Kudo, Masashi; Sugimoto, Motokazu; Konishi, Masaru; Gotohda, Naoto; Taniguchi, Hiroya; Yoshino, Takayuki
Abstract: Despite reports on poor survival outcomes after hepatectomy for colorectal liver metastases (CRLM) with BRAF V600E mutation (m BRAF ) exist, the role of m BRAF testing for technically resectable cases remains unclear. A single‐center retrospective study was performed to investigate the survival outcomes of patients who underwent upfront hepatectomy for solitary resectable CRLM with m BRAF between January 2005 and December 2017 and to compare them with those of unresectable cases with m BRAF . Of 172 patients who underwent initial hepatectomy for solitary resectable CRLM, m BRAF, RAS mutations (m RAS ), and wild‐type RAS / BRAF (wt RAS / BRAF ) were observed in 5 (2.9%), 73 (42.4%), and 93 (54.7%) patients, respectively. With a median follow‐up period of 72.8 months, mBRAF was associated with a significantly shorter OS (median, 14.4 months) than wt RAS / BRAF (median, not reached [NR]) (hazard ratio [HR], 27.6; p < 0.001) and m RAS (median, NR) (HR, 9.9; p < 0.001), and m BRAF had the highest HR among all the indicators in the multivariable analysis (HR, 17.0; p < 0.001). The median OS after upfront hepatectomy for CRLM with m BRAF was identical to that of 28 unresectable CRLM with m BRAF that were treated with systemic chemotherapy (median, 17.2 months) (HR, 0.78; p = 0.65). When technically resectable CRLM are complicated with m BRAF, its survival outcome becomes as poor as unresectable cases; therefore, those with m BRAF should be considered as oncologically unresectable. Patients with CRLM should undergo pre‐treatment m BRAF testing regardless of technical resectability. Clinical trial registration number: UMIN000034557. Abstract : A single‐center retrospective study was performed to investigate the survival outcomes of patients who underwent upfront hepatectomy for solitary resectable CRLM with BRAF V600E mutation between January 2005 and December 2017 and to compare them with those of unresectable cases with the mutation. When technically resectable CRLM are complicated with BRAF V600E, its survival outcome becomes as poor as unresectable cases; therefore, those with the mutation should be considered as oncologically unresectable.